دبلوماسية المسألة الشرقية كأساس لاتفاقية سايكس ـ بيكو ـ سازانوف 1804-1920 "حالة كردستان" - توفیق, هۆگر طاهر (Sulaimani Journal for Humanities, 2018)
Abstract: The colonial conflict in the Middle East during the nineteenth century led to very complicated situation I twentieth century. Kurdistan was not too far from this conflict, but it was in more difficult circle. At first glance, it appears that the conflict of powers in the Middle East was only a reflection of major countries' conflict in the Europe continent. The follower of the situations in the European continent, which is called the century of nationalities in Europe, clearly sees that the conflict between the major countries in the European continent had reached to a very complicated stage. Europe has gone through many crises and wars engulfed the European roadmap, the first of these wars was the outbreak of the French Revolution in (1789) and the rise of Napoleon on the scene in the European continent (1799-1815). The events were upside down that made it impossible for the European politicians to control over the developments. Major European countries entered in the conflict which extended to the two American continents, Asia, and Africa. Kurdistan was within the power zones in which Britain and Russia were fighting for during the nineteenth century. Then, Germany entered the field of conflict after the composition of German unity in 1871 to bring other variables, such as the agreement which drew power zones among the major powers in the Middle East and they were: Britain, Russia, and France. This agreement which is called in history as (Sykes-picot Sazanav) , was not the result of chance, but has roots extending to the beginning of the nineteenth century. It was the formula that the allies were forced to accept to face the German expansion in the Europe and in the world.